Geographic isolation alone does not explain divergence of a group of orchid species across Brazil's campos rupestres sky-islandsIsolamento geográfico por si só não explica a divergência de um grupo de espécies de orquídeas nos campos rupestres do Brasil. (23rd January 2023) - Fiorini, Cecilia F; Borba, Eduardo Leite; Resende-Moreira, Luciana C; de Camargo Smidt, Eric; Knowles, L Lacey
Abstract: Mountains play a crucial role in the origin and maintenance of Neotropical biodiversity, but there are still unanswered questions about the diversification of the campos rupestres (CR), an herbaceous-shrubby sky-island vegetation in eastern South America. For orchids distributed across this disjunct rock habitat, difficulties with distinguishing morphological taxa add an additional challenge to disentangling the history of divergence. Here, we combined the power of ddRAD genomic data with broad sampling of Bulbophyllum sect. Didactyle (Orchidaceae), across the CR and other Neotropical outcrops, to estimate evolutionary relationships and evaluate the biogeography of the group's diversification. Although genetic lineages generally align with geographic disjunctions, we also observe distantly related lineages within some previously recognized species. For such taxa, their lack of monophyly and a shared regional divergence pattern suggests a complex history that may include unrecognized diversity. When viewed through the lens of morphological variability, our study raises intriguing questions about the persistence and permeability of species barriers among orchid populations. These results, in addition to the recency of the divergence history of B. sect. Didactyle, provide insights about hypothesized community level vs. species-specific paths of diversification across the Neotropical sky-islands of the CR.